Remembering dates of birth: Memory as a discursive process - Norvilas, Algis; Miller, Jeffrey (Psichologija, 2015)
In a descriptive study, participants were asked to recall family members’ dates of birth and describe their recall experience. The recall protocols were analyzed both in terms of the phenomenological method and performance measures. The phenomenological analysis showed that birth date recall was often mediated by referent objects that bore a logical relationship to the target date unit. Performance measures, for their part, revealed a close relationship between the use of a rule-based referent object and the recall accuracy for date of birth. Furthermore, these findings are discussed in relation to the memory for time of events literature, focusing especially on the equivalence and difference of reference objects and on the presence of scale effects.